2015
DOI: 10.1097/01.aoa.0000463841.47692.19
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Maternal Outcomes With Prolonged Second Stage of Labor

Abstract: Objective-To assess neonatal and maternal outcomes when when the second stage of labor was prolonged according to American College of Obstetricians and Gynecologists guidelines. Methods-Electronic medical record data from a retrospective cohort (2002-2008) from 12 U.S. clinical centers (19 hospitals), including 43,810 nulliparous and 59,605 multiparous singleton deliveries ≥ 36 weeks, vertex presentation, who reached 10 cm cervical dilation were analyzed. Prolonged second stage was defined as: nulliparous wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 7 publications
0
25
0
2
Order By: Relevance
“…2,3 Possible causes of fetal asphyxia include maternal hypotension, poor placental perfusion, uterine tetany, and compression of the umbilical cord. 4,5 Disclosure: The authors declare no conflicts of interest.…”
Section: Overview and Definitionsmentioning
confidence: 99%
“…2,3 Possible causes of fetal asphyxia include maternal hypotension, poor placental perfusion, uterine tetany, and compression of the umbilical cord. 4,5 Disclosure: The authors declare no conflicts of interest.…”
Section: Overview and Definitionsmentioning
confidence: 99%
“…19,23,90 Most, but not all, studies of the effect of second-stage length found little effect of duration per se on early neonatal outcome for second stages up to at least 3 hours, [90][91][92] but there is little information on long-term maternal or neonatal morbidity. Maternal infection and hemorrhage risk does tend to increase after very long second-stage labors, due in part to the associated high likelihood of cesarean or operative vaginal delivery.…”
Section: The Deceleration Phasementioning
confidence: 99%
“…Others have indicated an increased rate of neonates with abnormal umbilical artery gas [12,24] and lower Apgar score at birth [25,28,29] with delayed pushing compared to immediate pushing. A large retrospective study of 42,268 women who had vaginal births reported that epidural use among nulliparous and mulitparous women led to a longer median length of second stage and the 95th percentile is longer than reported in previous studies [27].…”
Section: Originalmentioning
confidence: 99%